Characterization of Resistance to Cereal Cyst Nematode, Agronomic Performance, and End-Use Quality Parameters in Four Perennial Wheat-Thinopyrum intermedium Lines - Cui, Lei; Ren, Yongkang; Zhang, Yanming; Tang, Zhaohui; Guo, Qing; Niu, Yuqi; Yan, Wenze; Sun, Yu; Li, Hongjie (Frontiers in Plant Science, 2020)
Perennial wheat is considered to be a practical way to increase the flexibility and profitability of sustainable agricultural system, as it can be either a forage grass or a grain crop. Four perennial wheat lines SX12-480, SX12-787, SX12-1150, and SX12-1269 were developed from a series of interspecific crosses between common wheat (Triticum aestivum, 2n = 42) or durum wheat (T. turgidum var. durum, 2n = 28) and the intermediate wheatgrass (Thinopyrum intermedium, 2n = 42). These lines were characterized by the vigorous regrowth for at least three years. The one- and two-year-old plants had higher grain yield potential than the three-year-old perennial plants. The decline of grain yield was associated with plant age-related effects on yield components. The perennial wheat lines were all resistant to both Heterodera avenae and H. filipjevi, the two distinct cereal cyst nematode species that occur in China, except that line SX12-787 exhibited moderate resistance only to H. avenae. The dual-purpose perennial wheat lines were evaluated for quality values of both defoliated grass and harvested grains in the form of amino acid profile, mineral concentration, and contents of protein and fiber. Difference in the quality profile was observed between the perennial lines. These perennial lines had an overall improved quality levels over those of the perennial wheat control Montana-2 (T. turgidum × Th. intermedium) and the annual wheat cultivar Jinchun 9. The amplification profiles of the molecular markers provided molecular evidence for the introgression of alien chromatin. Genomic in situ hybridization detected 16, 14, 14, and 12 Th. intermedium chromosomes in lines SX12-480 (2n = 48), SX12-787 (2n = 56), SX12-1150 (2n = 56), and SX12-1269 (2n = 54), respectively, in addition to either 32 or the complete set of wheat chromosomes. The four perennial wheat-Th. intermedium lines described here provide valuable sources of perennial wheat for the dual-purpose application of both grain and forage.